Quantitative economic impact assessment of invasive plant pests: What does it require and when is it worth the effort?. (March 2015) - Soliman, T.; Mourits, M.C.M.; Oude Lansink, A.G.J.M.; van der Werf, W.
Abstract: According to the International Plant Protection Convention and the World Trade Organization Agreement on the Application of Sanitary and Phytosanitary measures, any measure against the introduction and spread of new pests must be justified by a science-based pest risk analysis. Economic impact assessments are usually carried out using a qualitative approach, based on classifying the size of impact into five categories, from "minimal" to "massive". Whilst the qualitative approach may be adequate in many instances, it lacks transparency and demonstrable objectivity. A quantitative approach for economic impact assessment may improve transparency and strengthen the justification for measures, if taken, but requires additional work, and it requires specific data and models. This paper, first, compares the strengths and weaknesses of qualitative and quantitative approaches. Second, it clarifies the data and models needed to conduct a quantitative economic impact assessment to support a decision on the pest quarantine status or justify management measures. Third, it identifies the criteria for choosing the appropriate level of complexity, regarding the resolution, economic technique and time frame of the quantitative approach. The greater transparency and objectivity of the quantitative vis-a-vis qualitative economic impact assessment may enhance plant health policy and decision making at national and international regulatory bodies. However, uncertainties that are inherent to this approach may weaken this position. Hence, PRAs require a mixture of quantitative and qualitative approaches for assessing impacts and the exact balance of the two has to be case-specific. Highlights: We compare qualitative and quantitative economic impact assessments of plant pests. We clarify the required data and models for quantitative economic impact assessments. We provide criteria to select the appropriate level of complexity in the economic impact assessment. PRAs require a mixture of quantitative and qualitative impact assessment approaches. The mixture of the two impact assessment approaches has to be case specific.